An Overview of the Journal of Institute of Science and Technology: Problems, Challenges and Future Prospects - Budha, Prem Bahadur (Journal of Institute of Science and Technology, 2015)
In its inception, the Journal of Institute of Science (JIS) was published in 1978 which was transformed to the Journal of Institute of Science and Technology (JIST) after the 7th volume published in 1984. The journal publication was stopped from 1989 to 2001 and resumed again from 2002 onward. The journal was published in every two years’ interval from 2002 to 2012, but with current chief editor, two issues in a year have been published from 2013 onward. The number of papers in JIST ranges from 3 to 32 comprising 1 page of review paper (vol. 18(2) in 2014) to 27 (vol. 3 in 1980). The most of contributing authors in all issues are mainly from Nepal with some contributors from India, China, Japan, Australia, Israel, Norway, USA, UK, Sweden, Spain, and Germany. Although the high quality papers have been used in the journal, paper citation rate is very poor due to its limited circulation in the academic market. The present paper highlights the past and current problems, challenges and future prospects to publish the journal efficiently with a view to make it available to wide range of readers with better quality papers. Journal of Institute of Science and Technology, 2014, 19(2): 1-6